The monitoring system of a qualitative structure of special physical preparation in cross-country race on motorcycles with a side-car - Valeriy Druz; Maria Cherednichenko; Volodymyr Shishka; Victoria Gorinа (Kharkiv State Academy of Physical Culture, 2015)
Purpose: to develop and to prove methods of an assessment and a control of special physical preparation of motorcycle racers on motorcycles with a side-car. Material and Methods: the analytical synthesis of data of scientific literature, the construction and the use of special semantic spaces, the processing of video filming, the biomechanical analysis of the motive activity. Results: the analysis of the main difficulties is carried out which are arising in the achievement of good results of motorcycle racers on motorcycles with a side-car. Methods of an assessment of each of the making components of the system "a sportsman - a motorcycle - an environment" are defined, components of special physical preparedness which weren't lit in special literature earlier are established. Conclusions: methods of a quantitative assessment of qualitative characteristics of special physical preparedness are stated which can be used in all sports